2019
DOI: 10.3892/ol.2019.10167
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of EphA5 protein in gastric carcinoma and its clinical significance

Abstract: The aim of the present study was to evaluate ephrin type-A receptor 5 (EphA5) expression and its clinicopathological significance in gastric cancer. Gastric cancer tissues were analyzed by immunohistochemistry. The association between EphA5 expression and clinicopathological parameters, human epidermal growth factor receptor 2 (HER2) status and Ki-67 proliferation index was statistically analyzed. EphA5 expression was detected in all non-tumor gastric epithelia but was differentially expressed among gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…However, other previous studies proved that EphA5 was detected to be low-expressed in some other malignant tumors [6][7][8][9][10]. The low expression of EphA5 was associated with lymph node metastasis of breast cancer [10], colorectal cancer [7] and gastric cancer [6], indicating poor prognosis in colorectal carcinoma [7] and ovarian cancer [8]. Contradictory with the above reports, we found that high EphA5 expression implies a greater likelihood of regional lymph node metastasis and advanced tumor stage, while low EphA5 expression may be related to nerve invasion.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, other previous studies proved that EphA5 was detected to be low-expressed in some other malignant tumors [6][7][8][9][10]. The low expression of EphA5 was associated with lymph node metastasis of breast cancer [10], colorectal cancer [7] and gastric cancer [6], indicating poor prognosis in colorectal carcinoma [7] and ovarian cancer [8]. Contradictory with the above reports, we found that high EphA5 expression implies a greater likelihood of regional lymph node metastasis and advanced tumor stage, while low EphA5 expression may be related to nerve invasion.…”
Section: Discussionmentioning
confidence: 85%
“…And in high-grade hepatocellular carcinoma,the EphA5 gene was also demonstrated to be upregulated [15,16]. However, other previous studies proved that EphA5 was detected to be low-expressed in some other malignant tumors [6][7][8][9][10]. The low expression of EphA5 was associated with lymph node metastasis of breast cancer [10], colorectal cancer [7] and gastric cancer [6], indicating poor prognosis in colorectal carcinoma [7] and ovarian cancer [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that signal transduction by the EPHA7 receptor may activate the extracellular-signal-regulated kinase (ERK) signaling pathway that also involves MAP3K8 [86]. Upregulation of EPHA7 was observed in many cancers, including hepatocellular carcinoma, where it was associated with tumor progression, invasiveness, and metastasis [87]. MAP3K8 was described as a mediator of vemurafenib resistance of thyroid cancer stem cells [88].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in these genes have first been found in paragangliomas/pheochromocytomas. TENM3 and EPHA5 encode for proteins with important functions in neuronal cells and have been shown to be involved in tumorigenesis [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%